2016
DOI: 10.1039/c6ob00968a
|View full text |Cite
|
Sign up to set email alerts
|

Diacetoxyiodobenzene assisted C–O bond formation via sequential acylation and deacylation process: synthesis of benzoxazole amides and their mechanistic study by DFT

Abstract: An efficient method for the transformation of N-substituted-N'-benzoylthioureas to substituted N-benzoxazol-2-yl-amides using diacetoxyiodobenzene (DIB) is described in this work. The transformation follows the C-O bond formation leading to the benzoxazole derivative, due to oxidative dehydrogenation by DIB, instead of the expected C-S bond formation of the benzothiazole moiety. The C-O bond formation leading to benzoxazole is due to consecutive acylation and deacylation in conjunction with the reduction of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…1 Additional applications include their use as laser dyes, photoluminescents 2 and whitening agents. 3 Despite their importance, the synthetic methods require multistep procedures, the use of metal catalysts, [4][5][6][7] hypervalent iodine 8 or strong oxidizing agents. 9 Selenium, although the least abundant metal element on earth, plays a pivotal role in biological systems by means of its antioxidant properties.…”
mentioning
confidence: 99%
“…1 Additional applications include their use as laser dyes, photoluminescents 2 and whitening agents. 3 Despite their importance, the synthetic methods require multistep procedures, the use of metal catalysts, [4][5][6][7] hypervalent iodine 8 or strong oxidizing agents. 9 Selenium, although the least abundant metal element on earth, plays a pivotal role in biological systems by means of its antioxidant properties.…”
mentioning
confidence: 99%
“…However, the pore size of the β zeolite is small, which is not conducive to diffusing substances and is easy to cause carbon deposition. 28 The preparation of hierarchical zeolites is one of the methods to solve the above problems. 29 Kloetstra KR 30 et al first reported the synthesis of hierarchical zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…As a commonly used material for adsorption separation and catalysis, molecular sieves can be simply divided into three types: micropore, mesopore, and micropore. The pores with a diameter of less than 2 nm, 2-50 nm, and more than 50 nm were called micropores, mesopores, and macropores, respectively [1][2][3]. With the advancement of research, researchers have gradually discovered that molecular sieves of three pore size have their own characteristics.…”
Section: Introductionmentioning
confidence: 99%